Pearls, power, and predation: an ecological perspective on marine resource governance in ancient China - Shi, Ce; Liu, Yonglian (Frontiers in Marine Science, 2025)
In ancient China, pearls were considered a luxury item and a symbol of imperial power. The competition for pearl harvesting rights was essentially an ecological and spatial contest among central imperial authority, eunuch factions, and local elites. This struggle prominently revealed the complex interactions between power, ecology, and law. The imperial state’s predatory pearl-harvesting policies led to a sharp decline in pearl oyster populations in the Beibu Gulf, exacerbating ecological pressures that triggered plagues, the displacement of Tanka people, and a surge in piracy, ultimately creating a vicious cycle of “environmental collapse–social disorder.” Although the Ming dynasty imposed strict prohibitions on private pearl harvesting, the eunuch monopoly and the breakdown of law enforcement rendered these bans ineffective. The contest between local officials and central policies further exposed the profound contradiction between the “legislative ideal” and the “governance reality” within the imperial autocratic system. By integrating local historical records with official documents, this study examines the interplay of power, resources, and ecology in the historical pearl industry of the South China Sea. Such an environmental perspective not only sheds light on institutional transformations over time but also provides historical insights into the sustainable governance of marine resources today.